Strategies in Countering Hoax and Hate Speech in Indonesia - Bambang Hartono; I Ketut Seregig; Budi Wibowo (Sociological Jurisprudence Journal, 2021)
Hoax and Hate Speech are cyber-crimes that are closely related to ideological, political and religious issues. In Indonesia, just before the 2019 Presidential Election, this crime is very common, mainly used to attack political opponents. In this study, we provide several samples of Hoax and Hate Speech crimes, namely those with ideological, political and religious nuances. We consider these three crime samples to be sufficient to illustrate that Hoax and Hate Speech greatly influence the stability of domestic security. Based on the results of research conducted at the Directorate of Cyber Crime Enforcement of the Indonesian Police Criminal Investigation Agency, we can conclude that the strategic steps that must be taken to tackle Hoax and Hate Speech are Preventive Efforts in the form of Cyber Patrol, Hoax labeling, analyzing media opinion trends, dissemination positive news through text media, clarification and public information, security carried out by cover names, cover jobs, and cover stories, and countermeasures. Then, to provide a deterrent effect to the community, repressive efforts through law enforcement activities must be carried out including investigations by means of the Cyber Patrol to find cyber-crime, providing technical assistance and tactical investigations, investigating units in the region in order to uncover networks of cyber perpetrators, providing assistance in examining digital evidence, and cooperating by exchanging information for the purpose of researching and investigating cyber-crime. With the coping methods described above, especially inter-regional police cooperation that is centrally controlled by maximizing technology, the Indonesian police are able to uncover and dismantle networks of cyber-crime perpetrators that occur in Indonesia such as hoaxes, hate speeches and terrorism.